INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PERUSAHAAN CONSUMER GOODS - Mohammad Aryo Arifin (Universitas Tridinanti, 2020)
The purpose of this study examined the effect of intellectual capital on the financial performance companies in the consumer goods industry sector Indonesia Stock Exchange 2015-2019. Variables used in the research are value added capital coefficient (VACA), value added human capital coefficient (VAHU), structural capital value added (STVA) and return on assets (ROA). This research use statistical Eviews The result shows that there is significant influence of value added capital coefficient (VACA), value added human capital coefficient (VAHU) and structural capital value added (STVA) to return on asset (ROA) either partially and simultaneously. These results indicate that inttelctual capital has an impact on financial performance. The implication of this study is the company can increase its profitability by utilizing intellectual capital. Keywords: VACA, VAHU, STVA, ROA